Економічна політика адміністрації Р. Рейгана щодо СРСР (1981–1989 рр.) - Krysenko, Dmytro; Крисенко, Дмитро (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті висвітлюється стратегія і тактика Вашингтону щодо Москви у господарській сфері на завершальному етапі «холодної війни» впродовж двох президентських каденцій Р. Рейгана. Основну увагу приділено курсу США в контексті економічної блокади СРСР та організації дипломатичної підтримки цієї акції.The article highlights the strategy and tactics of Washington toward Moscow in the economic sphere to the final stage of the «cold war» during R. Reagan’s two presidential mandates. The main attention is paid to the U. S. course in the context of economic blockade of the Soviet Union and diplomatic support of this action. The policy in oil and gas, financial, and technological systems has been conteplated; dependence of internal and external stability of the Soviet Union on energy prices has been showed. It is established that the escalation of tensions in relations with the USSR, represented one of the consequences of «conservative turn» in the West of the 1980’s.
Economic Policy of the Reagan Administration Toward the USSR (1981–1989)
Keywords: США; СРСР; санкції; протистояння; нафта; торгівля; the USA; the USSR; sanctions; rivalry; oil; trade